The sense of unity in the Jameh Mosque of Varamin: a geometric analysis - Ahsani, Majid; Ismail, Sumarni; Fallah, Siyamak Nayyeri; Al-Ameen, Ali (Maulana Malik Ibrahim State Islamic University, 2023)
The Jameh Mosque of Varamin is one of the few structures manifesting a transformation from Iranian architecture toward Iranian-Islamic architecture. The study presented here tries to deal with some of the geometric principles implemented by Iranian architects to express the concept of unity. The research decodes the sacred architectural elements and illustrates the ideas used to design the Jameh Mosque of Varamin from different aspects. In the first step, geometric principles such as dynamic rectangles, the golden ratio, and the lute of Pythagoras have been discussed. In the second step, the mentioned geometric principles are adapted to the architectural documents of the building. In addition, the general form of the building and the location of the dome are determined, and the hierarchy beginning from the Mosque's entrance to the dome has been analyzed. The results show that the architects tried to induce unity and monotheism through sacred geometry in a predetermined hierarchy. Also, Findings indicate that the Jameh Mosque of Varamin can be considered the intersection of Iranian architectural ideals adapted and integrated with Islamic principles.